2003
DOI: 10.1245/aso.2003.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fluorodeoxyglucose Positron Emission Tomography in the Detection of Axillary Lymph Node Metastases in Patients With Early-Stage Breast Cancer

Abstract: This study demonstrates the limitations of FDG-PET in the detection of ALN metastases in patients with early breast cancer. In contrast, FDG-PET seems to be a specific method for staging the axilla in breast cancer. SN biopsy can be avoided in patients with positive FDG-PET, in whom complete ALN dissection should be the primary procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 21 publications
1
42
1
1
Order By: Relevance
“…There were seven studies assessing PET/CT [73][74][75][76][77][78][79] and 19 studies assessing PET alone. 44,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Eight PET studies used ALND as the reference standard for all patients, 44,73,77,84,87,89,92,95,[98][99][100][101] 12 studies used a mixture of ALND and SLNB, [74][75][76][78][79][80][81][82][83]86,88,91,[102]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were seven studies assessing PET/CT [73][74][75][76][77][78][79] and 19 studies assessing PET alone. 44,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Eight PET studies used ALND as the reference standard for all patients, 44,73,77,84,87,89,92,95,[98][99][100][101] 12 studies used a mixture of ALND and SLNB, [74][75][76][78][79][80][81][82][83]86,88,91,[102]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Fourteen studies presented data such that the patients analysed in this review were entirely early stage (stage I, II or IIIA), newly diagnosed and non-DCIS, 44,75,76,80,[83][84][85][86][87][88][89]92,94,97 while the remaining 12 studies comprised up to 20% of patients who did not meet these criteria. 73,74,[77][78][79]81,82,90,91,93,95,96 Eight studies consisted entirely of patients who were clinically node negative, 73,76,79,81,83,84,87,88 13 studies included a mixture of node-negative and node-positive patients, 44,74,77,78,80,85,86,[91][92][93][94]96,97 and in five studies nodal status was not reported. 75,...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the ability of 18 F-FDG PET to determine axillary lymph node metastasis in patients with breast cancer who undergo SLNB, Barranger et al [16] recruited 32 breast cancer patients with clinically negative axillary nodes. All of the patients underwent 18 F-FDG PET, SLNB, and complete ordinal ALND.…”
Section: Comparison Of 18 F-fdg Pet (Pet/ct) and Slnb For Detecting Rmentioning
confidence: 99%